2015
DOI: 10.1186/s12909-015-0509-9
|View full text |Cite
|
Sign up to set email alerts
|

The effectiveness of a shared conference experience in improving undergraduate medical and nursing students’ attitudes towards inter-professional education in an Asian country: a before and after study

Abstract: BackgroundIn recent years, increasing emphasis has been placed on the importance of collaboration within multi-disciplinary healthcare teams, so as to facilitate holistic patient care and thus allow improved treatment outcomes. There is hence an urgent need to educate healthcare undergraduates early in their professional careers on the importance of and complexities involved in cooperating with counterparts from other allied healthcare professions. In conjunction with this, a milestone student-led conference f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

4
27
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(31 citation statements)
references
References 14 publications
4
27
0
Order By: Relevance
“…The relationship between RIPLS and IEPS indicated that preparing for interdisciplinary learning may promote appropriate professional attitudes in the students, emphasize conventional perceptions of other professions. As compare to another study Inter-professional education is extremely important in increasing a readiness in students to work with other healthcare students (Chua et al, 2015). Present study findings showed strong positive correlation between readiness and perception of students for interprofessional learning.…”
Section: Discussionsupporting
confidence: 59%
“…The relationship between RIPLS and IEPS indicated that preparing for interdisciplinary learning may promote appropriate professional attitudes in the students, emphasize conventional perceptions of other professions. As compare to another study Inter-professional education is extremely important in increasing a readiness in students to work with other healthcare students (Chua et al, 2015). Present study findings showed strong positive correlation between readiness and perception of students for interprofessional learning.…”
Section: Discussionsupporting
confidence: 59%
“…The mean baseline RIPLS score is comparable with a study by Chua et al conducted in Singapore. (26) Chua et al also found higher baseline RIPLS scores for medical undergraduates compared to other groups of undergraduates, a nding also noted in this study and another done in a culturally similar country. (26,29) This is contrary to other studies which found that medical students had a lower RIPLS score.…”
Section: Discussionsupporting
confidence: 87%
“…(26) Chua et al also found higher baseline RIPLS scores for medical undergraduates compared to other groups of undergraduates, a nding also noted in this study and another done in a culturally similar country. (26,29) This is contrary to other studies which found that medical students had a lower RIPLS score. (30,31) Chua et al also found that prior exposure to IPE resulted in signi cantly higher RIPLS scores.…”
Section: Discussionsupporting
confidence: 87%
“…Under the Interprofessional relationship skills domain, we identified a new sub-domain "demonstrated collegiality". According to Hofstede's cultural dimension theory, Asians tend to be more collectivist compared to Western populations [18], and this was highlighted in the new sub-domain "demonstrated collegiality", which demonstrates the faculty's perception of the increasing importance of team-based care and collaboration between various healthcare professionals, whose opinions should be respected [34,35]. The importance of collegiality was also highlighted in the study by Chandratilake et al who showed that working with one's colleagues towards common goals was deemed to be important in European and North American countries [21].…”
Section: Discussionmentioning
confidence: 99%